2020
DOI: 10.3390/su12020728
|View full text |Cite
|
Sign up to set email alerts
|

The Importance Given to Food Naturalness Attributes by Millennial University Students

Abstract: So-called natural food is one of the most significant current trends in the food business. Despite this trend, previous research on the measurement of naturalness has made no distinction between different groups of consumers. Therefore, the objective of this study is to explore the attributes important to millennial university students when evaluating food naturalness. The study is based on a questionnaire administered to a sample of 372 respondents. Using a partial least square (PLS) methodology, it performs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…Other research has explored naturalness in relation to food production, revealing some variation in how the term is understood [ 37 ]. For example, Jorge et al [ 38 ] surveyed university students regarding food naturalness and found that three factors emerged: how the food is produced (e.g. ingredients, additives, preservatives), how the food is grown (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other research has explored naturalness in relation to food production, revealing some variation in how the term is understood [ 37 ]. For example, Jorge et al [ 38 ] surveyed university students regarding food naturalness and found that three factors emerged: how the food is produced (e.g. ingredients, additives, preservatives), how the food is grown (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Participants discussed naturalness as a benefit of “small farms”. Previous research has shown that people sometimes conflate small farms with naturalness [ 3 ]; this is discussed in Jorge et al’s [ 38 ] work as an aspect of how food is grown. The present study did not explicitly assess attitudes in relation to the aspect of farm size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this study adopts the approach that considers university students represent young consumers well [25,105], and the contributions of other authors regarding the verification of personal user data of the web community have been taken into account [106]. In recent generational studies, samples of students belonging to only one university center have been used, including Spanish academic centers [107,108]. The sample initially included 637 subjects (43.45% men and 56.55% women), which is an appropriate size when structural equations are used [109].…”
Section: Data Collection and Sample Profilementioning
confidence: 99%
“…This claim is commonly linked to 'old-style family-farm food' production [10], which is capable of better preserving food naturalness [11] and authenticity [12]. However, recent studies focusing on the millennial generation have shown evidence that such consumers do not necessarily link traditional food products with natural food products [13]. This previous evidence raises questions about the importance these consumers place on the specific case of traditional wine and conditions for attracting wine interest.…”
Section: Introductionmentioning
confidence: 99%